PERBEDAAN PERUSAHAN PENCIPTA ECONOMIC VALUE ADDED POSITIF DENGAN ECONOMIC VALUE ADDED NEGATIF - Suripto Suripto (University of Merdeka Malang, 2008)
This research was to explain and analyze the different variable of Inflation Rate,Exchange Rate, Interest Rate, Ratio Plant Asset, Size Measure Company, Profitability, Growth ,LD / E, TD / TA, Stock of Return, Book To Market between company having Economic ValueAdded ( Positive ) and company having Economic Value Added ( Negative ). Analysis which wasused in this research was multivariate analysis of variant (MANOVA). There was different variableof Inflation Rate, Exchange Rate, Interest Rate, Ratio Plant Asset, Size Measure Company,Profitability, Growth , LD / E, TD / TA, Stock of Return, Book To Market between companyhaving Economic Value Added ( Positive) and negative EVA. However, by partial, only differentsale size was significant